2022
DOI: 10.1093/g3journal/jkac063
|View full text |Cite
|
Sign up to set email alerts
|

Mutation, selection, and the prevalence of the Caenorhabditis elegans heat-sensitive mortal germline phenotype

Abstract: Caenorhabditis elegans strains with the heat-sensitive mortal germline phenotype become progressively sterile over the course of a few tens of generations when maintained at temperatures near the upper range of C. elegans’ tolerance. Mortal germline is transgenerationally heritable, and proximately under epigenetic control. Previous studies have suggested that mortal germline presents a relatively large mutational target and that mortal germline is not uncommon in natural populations of C. elegans. The mortal … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…We only used such polymorphisms in the GWAS (see Methods). We included data collected by Saber et al (2022) and used either the full strain set (Fig EV1B), or a restricted set (Fig 1E and F) without the divergent Pacific area strains (as defined by Crombie et al , 2019, and Lee et al , 2021, Table EV1). Using the restricted set of 113 strains, we found that variation in the number of generations to sterility was significantly associated with genetic variation in a region of chromosome III located around 5 Mb (Fig 1E).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We only used such polymorphisms in the GWAS (see Methods). We included data collected by Saber et al (2022) and used either the full strain set (Fig EV1B), or a restricted set (Fig 1E and F) without the divergent Pacific area strains (as defined by Crombie et al , 2019, and Lee et al , 2021, Table EV1). Using the restricted set of 113 strains, we found that variation in the number of generations to sterility was significantly associated with genetic variation in a region of chromosome III located around 5 Mb (Fig 1E).…”
Section: Resultsmentioning
confidence: 99%
“…Mutation accumulation lines can be used to measure the ease with which a given phenotype can be altered by de novo mutation and, by comparison with natural populations, allow inference of natural selection. With this aim in mind, Saber et al (2022) used spontaneous mutation accumulation lines in C. elegans starting from two wild‐derived strains with a non‐Mrt phenotype. They found a single mutation line with a strong Mrt phenotype, likely caused by a frameshifting insertion in nrde‐2 , and none with a weak Mrt phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antoine Cook et al, 2017;Crombie et al, 2019;Evans, van Wijk, et al, 2021;Gaertner & Phillips, 2010;Lee et al, 2021). Natural genetic variation exists for practically any organismal trait measurable in C. elegans (Andersen & Rockman, 2022), for example: responsiveness to toxins, metals, drugs, and other stressors (Dilks et al, 2021;Evans & Andersen, 2020;Evans, Wit, et al, 2021;Hahnel et al, 2018;Na et al, 2020;Webster et al, 2019;Zdraljevic et al, 2019;Zdraljevic et al, 2017); behavior (Bendesky et al, 2012;Ghosh et al, 2015;McGrath et al, 2009); transgenerational mortality traits (Frezal et al, 2018;Saber et al, 2022); and efficiency in RNA interference (RNAi) (Elvin et al, 2011;Felix, 2008;Felix et al, 2011;Paaby et al, 2015;Tijsterman et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…However, C. elegans harbors significant intraspecific genetic diversity (A. Barriere & M. A. Felix, 2005; Antoine Barriere & M. A. Felix, 2005; Crombie et al, 2019; Lee et al, 2021; Andersen et al, 2012), and in the last decade C. elegans has also been established as a powerful system for elucidating connections between genotype and phenotype (Andersen et al, 2012; Andersen & Rockman, 2022; A. Barriere & M. A. Felix, 2005; Antoine Barriere & M. A. Felix, 2005; Cook et al, 2017; Crombie et al, 2019; Evans, van Wijk, et al, 2021; Gaertner & Phillips, 2010; Lee et al, 2021). Natural genetic variation exists for practically any organismal trait measurable in C. elegans (Andersen & Rockman, 2022), for example: responsiveness to toxins, metals, drugs, and other stressors (Dilks et al, 2021; Evans & Andersen, 2020; Evans, Wit, et al, 2021; Hahnel et al, 2018; Na et al, 2020; Webster et al, 2019; Zdraljevic et al, 2019; Zdraljevic et al, 2017); behavior (Bendesky et al, 2012; Ghosh et al, 2015; McGrath et al, 2009); transgenerational mortality traits (Frezal et al, 2018; Saber et al, 2022); and efficiency in RNA interference (RNAi) (Elvin et al, 2011; Felix, 2008; Felix et al, 2011; Paaby et al, 2015; Tijsterman et al, 2002).…”
Section: Introductionmentioning
confidence: 99%